Dampak Kenaikan Harga BBM 2005 pada Pola Konsumsi Masyarakat di Wilayah Purwokerto - Dian Purnomo Jati; Rakhmat Priyono (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2007)
Gasoline consumption has been daily needs especially in city area. Price fluctuation on this commodity will impact gradually to good and service market equilibrium. The shock will so impact to consumption ability on their transaction, which it means downward consumers buying potency. Government policy that increased price gasoline, October 1, 2005, it was almost 100%, had significant effect to consumption optimism decreasing in Purwokerto area. They tended to delay and might reschedule their needs. Also, gasoline price increase has impacted to create pessimistic behavior on people expectation. They had opinion that six months letter, on the future, they probably will not make persistence consumption like they did before. The decreasing of consumer’s optimism was gathered by pessimistic response on current economics conditions. Therefore, positive stimulation to create back consumers buying potency should be government agenda to normalize economics condition. Keywords: price gasoline, consumers buying potency, expectation.